Hijacking of the Host SCF Ubiquitin Ligase Machinery by Plant Pathogens - Magori, Shimpei; Citovsky, Vitaly (Frontiers in Plant Science, 2011)
The SCF (SKP1-CUL1-F-box protein) ubiquitin ligase complex mediates polyubiquitination of proteins targeted for degradation, thereby controlling a plethora of biological processes in eukaryotic cells. Although this ubiquitination machinery is found and functional only in eukaryotes, many non-eukaryotic pathogens also encode F-box proteins, the critical subunits of the SCF complex. Increasing evidence indicates that such non-eukaryotic F-box proteins play an essential role in subverting or exploiting the host ubiquitin/proteasome system for efficient pathogen infection. A recent bioinformatic analysis has identified more than 70 F-box proteins in 22 different bacterial species, suggesting that use of pathogen-encoded F-box effectors in the host cell may be a widespread infection strategy. In this review, we focus on plant pathogen-encoded F-box effectors, such as VirF of Agrobacterium tumefaciens, GALAs of Ralstonia solanacearum, and P0 of Poleroviruses, and discuss the molecular mechanism by which plant pathogens use these factors to manipulate the host cell for their own benefit.